Antibacterial effect of Pylantus niruri L. (Meniran) from Indonesia toward Staphylococcus epidermidis and Phytochemical Screening - Em Sutrisna; Sri Wahyuni; Devi Usdiana R; Noor Fadzilah Zulkifli; Nazefah Abd Hamid; Farah Wahida Harun; Siti Salhah Othman; Dzulfadli Rosli (A and V Publications, 2025)
Indexed